Addressing food security through cooperative urban farming - Tim McDermott (Urban Food Systems Symposium, 2020)
Ohio ranks well above the national average in the prevalence of food insecurity. According to the USDA-ERS, 1 in 7 households are considered food insecure. In Franklin County alone (Columbus and metro area), 1 in 5 children are food insecure. Urban agriculture is positioned to potentially address this issue by increasing availability of fresh produce and economic opportunities in disadvantaged areas, but challenges for urban growers abound - high cost of entry, land tenure, lack of skills and knowledge, access to and consistency of markets, to name a few. The Ohio State University (OSU) is investing in a systems approach to addressing neighborhood food insecurity and the challenges faced by urban growers through the Initiative for Food and AgriCultural Transformation’s (InFACT) Institution-Supported Agriculture (Buckeye ISA). The Buckeye ISA is embedded in the five Franklin County neighborhoods identified by the joint City-County Local Food Action Plan as critically economically challenged. Too many of these neighborhood residents are classified as food insecure with poor access to fresh nutritious food and must rely on the emergency food system. The project engages households with children 8 years and under in these neighborhoods and leverages local resources from government agencies, business, non-profit and institutional partners. By providing education, materials support and mentorship around local food production, the Buckeye ISA increases families' ability to provide for their personal and family food security. Growing food in urban areas and connecting urban consumers with agriculture requires systemic solutions to challenges such as knowledge gaps, materials support, and lack of access to productive land. By leveraging existing partnerships, innovative programming, and grower network development, we aim to develop an alternative path for urban farmers and communities that is both sustainable and resilient.
Keywords: COVID-19; education; agility; adaptation; food production